Mating strategies and multiple paternity, assessed by microsatellites, of the dispersal-limited, ectoparasitic tree-hole tick, Ixodes arboricola. Issue 9 (August 2016) - Van Oosten, A.R.; Matthysen, E.; Heylen, D.J.A.
Graphical abstract: Highlights: Multiple mating is common in ticks, but multiple paternity is largely unexplored. We examined mating and paternity in the nidicolous tick Ixodes arboricola . Male ticks prefer mating with engorged females and exhibit mate guarding. There is multiple paternity but, overall, no precedence of a particular male. Abstract: Multiple mating is common among ticks, a large group of haematophagous ectoparasites, but multiple paternity has rarely been investigated. Multiple paternity may be common because the resultant increased genetic diversity allows ticks to rapidly evolve in relation to host responses and increases colonisation potential in novel habitats. Knowledge concerning mating systems is important because ticks may have profound effects on their hosts and are the principal transmitters of many pathogenic agents. In the current study, we investigated the mating system of the nidicolous tick Ixodes arboricola . These ticks attach to their bird hosts in the nest, which restricts gene flow but facilitates finding a partner off-host. Having genetically variable offspring may be beneficial for ticks which may encounter very different conditions when dispersed to the nest of another host type. We conducted an experiment in which female ticks fed on great tit nestlings and mated with two males in three treatments of the females: mating with both males before feeding, mating with one male before and the other male after feeding, or mating with both males after feeding. We investigated paternity with microsatellites. In a complementary experiment we investigated male preference for unfed or engorged females, and measured mating duration. We predicted (i) there would be multiple mating by I. arboricola males and females, leading to multiple paternity, and (ii) males would prefer to mate with engorged females and those matings would last longer because engorged females present a higher probability of successful reproduction. We found multiple paternity within clutches but no indications of sperm precedence. Males preferred to mate with engorged females and those matings lasted significantly longer, even including attachment beyond egg deposition. We suggest such mate guarding and male preference for mating after feeding is adaptive because there is no first male precedence. Male preference for mating after feeding may also be adaptive because dispersal is low and females are available after the blood meal.